LIMITS AND OPERATIONAL EVALUATION OF THE SPAWNERS ESCAPEMENT TO THE SPAWNING GROUNDS AS TOOLS FOR PROSPECTIVE AND SHORT-TERM MANAGEMENT OF THE PACIFIC SALMON STOCKS IN THE RIVERS OF THE FAR-EASTERN FISHERIES BASIN - E. A. Shevlyakov; M. G. Feldman; V. I. Ostrovsky; V. V. Volobuev; A. M. Kaev; E. V. Golub; E. I. Barabanshchikov; I. S. Golovanov (Известия ТИНРО)
The major aspects of density regulation of the pacific salmons spawning are analyzed. Uncertainty of the ecological parameters considered traditionally as indicators of the salmons reproduction efficiency is discussed. If the method of the efficient spawning density is applied to the whole area of spawning grounds, without examination of conditions for spawning, false conclusions on optimum abundance of the spawners could be made. Clear criteria of the spawning grounds environments suitable for spawning are necessary for correct evaluation of the density factor for regulation the population abundance. Efficient escapement to the spawning grounds could be determined adequately by analysis of the reproduction curve. Critical analysis of tools for short- and long-term management of the salmon fishery is presented. Variants of compromise decisions for the multispecies fishery are discussed. The optimal escapement to the spawning grounds in not an absolute norm, but is a statistical parameter used for reaching the maximum production. Conflict between the strategies of saving the reproduction basis of salmon populations and the landing increase by fishing companies is demonstrated. Criteria and algorithm of short-term corrections of the salmon catches during the fishery campaign are provided. Major local units of the pacific salmon stocks in the Far East of Russia are outlined; biological parameters necessary for management of their exploitation are defined. Numbers of the spawners necessary for local and general support of spawning stocks for 5 commercial species of pacific salmons are evaluated to provide the most effective and sustainable natural reproduction of the stocks in the Russian part of the North Pacific.